Timing of menarche and pubertal growth patterns using the QEPS growth model - Gårdstedt-Berghog, Jenni; Niklasson, Aimon; Sjöberg, Agneta; Aronson, A. Stefan; Pivodic, Aldina; Nierop, Andreas F. M.; Albertsson-Wikland, Kerstin; Holmgren, Anton (Frontiers in Pediatrics, 2024)
Objectives: To explore timing of menarche, post-menarcheal growth, and to investigate the impact of various variables on menarcheal age, post-menarcheal and pubertal growth.Study Design: This longitudinal community population-based study analyzed pubertal growth and menarcheal age in 793 healthy term-born Swedish girls, a subset of the GrowUp1990Gothenburg cohort. Timing of menarche and post-menarcheal growth were related to variables from the QEPS (quadratic-exponential-pubertal-stop) growth model, birth characteristics, and parental height. Multivariable models were constructed for clinical milestones; at birth, age 7 years, pubertal growth onset and mid-puberty.Results: Menarche aligned with 71.6% (18.8) of the QEPS-model's specific pubertal growth function, at a mean age of 13.0 (1.3) years, ranging from 8.2 to 17.2 years. Post-menarcheal growth averaged 8.0 (4.9) cm, varying widely from 0.2 to 31.1 cm, decreasing with later menarche. Significant factors associated with menarcheal age included height at 7 years, childhood body-mass index (BMI), parental height, and QEPS-derived pubertal growth variables. Multivariable models demonstrated increasing explanatory power for each milestone, explaining 1% of the variance in menarcheal age at birth, 8% at age 7 years, 44% at onset of pubertal growth and 45% at mid-puberty.This study underscores the strong link between pubertal growth and age at menarche. Data available at start of puberty explain 44% of the variation in menarcheal age, apparent on average 3.2 years before menarche. Additionally, the study shows a previously seldom noticed wide variation in post-menarcheal height gain from 0.2 to 31.1 cm.